FEM modelling of heat transfer in ceramic material synthesis process under electric arc. - Pozo Morejón, Juan; García Jacomino, Jorge; González, Gema; Quintana Puchol, R. (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
In this paper, a general characterization of ceramic materials and SiC-Al2O3-specific obtained by Self-sustained Synthesis of High Temperature Assisted by Electric Arc (EA-SHS) process developed by re- searchers at CIS. It describes the physical and thermal characteristics of the materials involved in the re- action system, raw materials SiO2-Al-C and furnace materials - to perform the finite element model (FEM) and simulated by ANSYS-MULTIPHYSICS software transfer heat produced by a power source to the pickup point of the reactants and other elements of the oven. It declares the heat transfer by convection and radiation from high temperature process. The MEF obtained model was run with various intensities of the heat source (100, 80, 60 and 40 A), observing the behaviour of the temperature vs. time at different points of the pellet and providing technical criteria for carrying out the synthesis of the ceramic material.